Pengaruh Jumlah Pelaku Usaha Terhadap Stabilitas Harga Dalam Model Oligopoli - Ariel Muhammad Jadhi Sembiring; Bona Vintura Suyana Pandiangan; Gresia Apriyani; Siti Sarah Tumangger; Sri Ramadhani Siregar (Insan Zenius Ilmiah, 2025)
This research aims to analyze the influence of the number of business owners on price stability in an oligopoly market structure. In an oligopoly market, the interaction between business entities plays a crucial role in determining prices. A small number of businesses tends to create price instability due to interdependent competitive strategies, including potential collusion or aggressive price reactions. Conversely, as the number of businesses increases, competition becomes fiercer and the tendency for prices to stabilize also increases. This research uses a descriptive qualitative approach thru literature studies and microeconomic theory analysis using the Cournot and Bertrand models. The study results show that market structure significantly determines price formation patterns, with the number of business operators being an important variable in creating market efficiency and price stability. Additionally, strategic interdependence between firms explains the phenomenon of price stickiness and extreme fluctuations in oligopolistic markets. This finding contributes to understanding the dynamics of oligopoly and the policy implications for regulating a healthier and more competitive market structure. This research also recommends the importance of regulation to increase the number of business actors in order to foster a fair competitive climate and stable prices, thereby protecting the interests of consumers broadly.